2017
DOI: 10.1021/jacs.7b11493
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (−)-Majucin and (−)-Jiadifenoxolane A, Complex Majucin-Type Illicium Sesquiterpenes

Abstract: We report the first chemical syntheses of both (−)-majucin and (−)-jiadifenoxolane A via 10 net oxidations from the ubiquitous terpene (+)-cedrol. Additionally, this approach allows for access to other majucin-type sesquiterpenes, like (−)-jiadifenolide, (−)-jiadifenin, and (−)-(1R,10S)-2-oxo-3,4-dehydroxyneomajucin (ODNM) along the synthetic pathway. Site-selective aliphatic C(sp3)-H bond oxidation reactions serve as the cornerstone of this work which offers access to highly oxidized natural products from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…In 2009, we disclosed a proof-of-concept to efficiently access highly oxidized terpenes that holistically mimics this underlying logic of biosynthesis . Two-phase terpene synthesis logic, despite lacking convergency, could be applied to concise syntheses of complex systems such as ingenol, phorbol, thapsigargin, and others. , Application of this strategy to the non-skeletally rearranged taxanes, of which 1 resides at the apex of structural complexity, remained aspirational for the past decade. This can be visualized in Figure , with a hypothetical retro­synthetic pyramid for the two-phase synthesis of 1 requiring a chemist to navigate no less than nine different C–O bond-forming steps from a minimally oxidized taxane precursor such as taxadienone ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, we disclosed a proof-of-concept to efficiently access highly oxidized terpenes that holistically mimics this underlying logic of biosynthesis . Two-phase terpene synthesis logic, despite lacking convergency, could be applied to concise syntheses of complex systems such as ingenol, phorbol, thapsigargin, and others. , Application of this strategy to the non-skeletally rearranged taxanes, of which 1 resides at the apex of structural complexity, remained aspirational for the past decade. This can be visualized in Figure , with a hypothetical retro­synthetic pyramid for the two-phase synthesis of 1 requiring a chemist to navigate no less than nine different C–O bond-forming steps from a minimally oxidized taxane precursor such as taxadienone ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the elusive C–H oxygenation in biosynthetic proposals, the derivatization through an olefin intermediate would be much more doable in achieving chemo- and stereoselectivity. We anticipated that the olefinic compound 6 could be generated through site-selective desaturation from dilactone 5 .…”
Section: Resultsmentioning
confidence: 97%
“…(À)-Majucin and (À)-jiadifenoxolane A. Maimone et al reported the rst synthetic route to complex majucin-type natural products (À)-majucin ((À)-320) and (À)-jiadifenoxolane A ((À)-321) starting from the abundant feedstock (+)-cedrol ((+)-304). 284,[476][477][478][479] The synthesis commenced with a Suárez oxidation, followed by a hydroboration/double oxidation Overall, 13 oxidations were employed while three reduction steps were necessary to achieve the correct oxidation state and for stereochemical adjustments. Favorable aspects in the light of "green" chemistry are the use of a photocatalyzed reaction, and of green solvents (acetone, H 2 O, MeOH), yet undesired solvents like CCl 4 or PhCF 3 also occur.…”
Section: Terpenesmentioning
confidence: 99%